Conservation and divergence of meiotic DNA double strand break forming mechanisms in Arabidopsis thaliana. Issue 17 (30th August 2021) - Vrielynck, Nathalie; Schneider, Katja; Rodriguez, Marion; Sims, Jason; Chambon, Aurélie; Hurel, Aurélie; De Muyt, Arnaud; Ronceret, Arnaud; Krsicka, Ondrej; Mézard, Christine; Schlögelhofer, Peter; Grelon, Mathilde
Abstract: In the current meiotic recombination initiation model, the SPO11 catalytic subunits associate with MTOPVIB to form a Topoisomerase VI-like complex that generates DNA double strand breaks (DSBs). Four additional proteins, PRD1/AtMEI1, PRD2/AtMEI4, PRD3/AtMER2 and the plant specific DFO are required for meiotic DSB formation. Here we show that (i) MTOPVIB and PRD1 provide the link between the catalytic sub-complex and the other DSB proteins, (ii) PRD3/AtMER2, while localized to the axis, does not assemble a canonical pre-DSB complex but establishes a direct link between the DSB-forming and resection machineries, (iii) DFO controls MTOPVIB foci formation and is part of a divergent RMM-like complex including PHS1/AtREC114 and PRD2/AtMEI4 but not PRD3/AtMER2, (iv) PHS1/AtREC114 is absolutely unnecessary for DSB formation despite having a conserved position within the DSB protein network and (v) MTOPVIB and PRD2/AtMEI4 interact directly with chromosome axis proteins to anchor the meiotic DSB machinery to the axis.